Clothing influence on the mood of selected dysthymic females - Engracia, Karinna Laura R.; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
Depression as a growing mental health issue in the Philippines (Babao, 2015) has attracted the attention of the Philippine Congress, which have recently approved the Mental Health Act 2017, thus providing every Filipino with the right to acquire free mental health services in order to care and provide for their mental well-being (Senate of the Philippines, 2017). By studying the relationship between clothing and mood (Venkatesh, Vivekanandan and Balaji, 2012), this undergraduate thesis aimed to identify how clothing is used by dysthymics in order to improve their low moods in order to aid depressives through a practical means of therapy. The study of five purposively selected participants comprises of three parts, a wardrobe study, 30-day experiment and interview, where each respective part acquires a more specific understanding of how the participants dress in relation to their mood. Based on the data collected, the relationship between mood and clothes is moderately positive, wherein the clothing attributes of color, fit, fabric, print, memory, and social feedback are most regarded when selecting pieces during a low mood. Based on the analysis, participants typically prioritize comfort in terms of breathability, mobility, and belongingness when selecting pieces in order to calm their mental state; calming the mental state is delegated as the main role of clothing. For further research on the study, the researcher recommends isolating the different clothing pieces from one another as well as studying other sexes, and types of depression.
Submitted January 2018.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing and dress -- Philippines; Clothing and dress -- Psychological aspects